Association of inflammatory bowel disease with ankylosing spondylitis and rheumatoid arthritis: A nationwide population-based study. Issue 3 (4th May 2017) - Bae, Jung Min; Choo, Ji Yoon; Kim, Ki-Jo; Park, Kyung-Su
Abstract: Objectives : Tantalizing connections between autoimmune rheumatic diseases (ARDs) and inflammatory bowel disease (IBD) have become evident with regard to their genetic and immunologic background. However, the association between these two disease entities remains unclear. The aim of this study is to investigate the association between each ARD and IBD. Methods : A nationwide population-based cross-sectional study was performed using the Korean National Health Insurance Claims database. The data of patients with IBD and age- and sex-matched controls between 2009 and 2013 were collected from the database. The prevalence of ARDs, including systemic lupus erythematosus (SLE), inflammatory myositis (polymyositis and dermatomyositis), systemic sclerosis (SSc), Sjögren's syndrome (SjS), ankylosing spondylitis (AS), and rheumatoid arthritis (RA), was determined. The associations between each ARD and IBD were analyzed using multivariate logistic regression models. Results : A total of 40, 843 IBD patients (28, 197 patients with ulcerative colitis and 12, 646 with Crohn's disease) and 122, 529 controls were enrolled. The nonstratified analysis revealed that patients with IBD had significant risk of being concomitantly affected by AS (odds ratio [OR] 5.140, 95% confidence interval [95% CI] 4.069–6.492) and RA (OR: 3.474, 95% CI: 2.671–4.519) after adjusting for age and sex. No significant association was observed between IBD and other ARDs including SLE, inflammatory myositis, SSc, and SjS. Conclusion : IBD is significantly associated with AS and RA in the large-scaled population-based study. This result suggests that etiopathogenesis of IBD might be shared with AS and RA.